A novel distributing–collecting on-line insulation monitoring system and line selection technology for the DC supply system - Feng, Chen; Ye, Pingfeng; Gao, Zhengzhong; Jiang, Haiyang; Zang, Xiangyu; Zhang, Xiangxing (Frontiers in Energy Research, 2023)
At present, the power supply system used byof 5G base stations is a micro smart grid, it generally uses 240V DC power supply with multiple branches, and leakage accidents will threaten personal and property safety, so it is vital to identify the fault line accurately and remove the faults rapidlyafter the fault occurs. In this paper, the leakage phenomenon of transmission lines in HVDC power supply system of 5G communication base station is studied. To address the issue of multi-branch line leakage diagnosis and line selection in 240V DC system, a new distributed DC insulation monitoring and fault line selection technology and system are proposed. The distributed DC insulation monitoring line selection technology is used to collect the leakage current of each branch by setting a unique single-core DC leakage transformer, and process the signal centrally. In addition, a high resistance bridge switchgear is added to the bus bar. By using According to the different leakage current caused by the imbalance of the bridge before and after the switch, the insulation resistance electrodes to the ground is calculated accurately, which solves the problem that the current technology cannot judge the fault of the positive and negative electrodes to the ground at the same time. Through simulation and prototype experiment two waysThrough simulation, the feasibility of this technology and system device in line insulation monitoring and line selection of HVDC communication base station power supply system is verified.